A representação social de professores do ciclo de alfabetização sobre o letramento: analisando sentidos e posicionamentos. - Almeida, Elaine Vieira de (2020)
This study aimed to analyze the social representation on the literacy of teachers in the literacy cycle of Fortaleza - CE. For this, we sought to describe initially describe the organizational structure of the elements that make up the central and peripheral systems of the social representation of teachers about literacy, establish meanings for the elements of teachers’social representation about literacy from the position they occupy in their central and peripheral systems, as well as to relate the organizational structure of the central and peripheral systems of the representation of teachers with the positions of these about the teaching of literacy. We are based on the assumptions of Moscovici's Theory of Social Representations (1978), based on the approaches of Abric (1994; 2001), Flament (0000) and Doise (2001), also using some assumptions of Denise Jodelet (2001). We also used contributions from Soares (2005; 2017), Kleiman (2008) and Mortatti (2004) on the concept of literacy and its different meanings, from the perspective of the New Studies of Literacy – NEL (STREET, 1984; 2000; 2014). The research is qualitative in nature, although we have used some quantitative procedures to outline scenarios whose numerical data contribute in a complementary way. The instruments and techniques used are based on the Central Nucleus Theory (ABRIC, 2001; 2003), which is: the free association of words, the hierarchization of items, the questioning technique, as well as semi-structured interviews with teachers of the literacy cycle of Fortaleza - CE. The results obtained suggest that, for these teachers, being literate implies building a knowledge about the social world from the appropriation of reading, as an activity of appropriation of the conventions of the alphabetic writing system. This understanding occurred after identifying world knowledge/reading as being the main element within the central nucleus of RS and the terms make social use and understanding as its adjunct elements, followed by the evocations reading and literacy as being the entrance of the peripheral system. The instability of these last two terms and the semantic particularizations presented by the assigned meanings distanced these cognitions from the centrality of representation. Based on this semantic organization, we identified two major positions brought by teachers in relation to the teaching of literacy: literacy as "starting line" and literacy as "finish line". According to the first, the teaching of literacy is made from the valorization of the students' previous knowledge, seen as a "box of elements" necessary for the learning of writing. The second suggests the teaching of literacy as a lens to see the world, this being a finish line in the learning of writing. Therefore, we conclude that the social representation of teachers on literacy, guided by the central element - knowledge/reading of the world - meets the functional demands related to the context of responses to proficiency goals established by the evaluation system of the municipal network of Fortaleza - CE. These meanings, individualized by the subjects, endorse a "literacy literacy" constituted in the dissociation between the processes of literacy and literacy, and the mastery of the alphabetic writing system is an initial phase and the social use of reading and writing something to be achieved at the end of the process.